A Study of the Current Position of Traditional Chinese Hanging Lanterns Among Young Chinese - Ming, Liew Yek; Mohd Nasseri, Edina; Husain, Abdul Halim (KnE Social Sciences, 2023)
Traditional Chinese lanterns were invented during the Eastern Han Dynasty and were originally intended to be sources of light. To most Chinese people, traditional Chinese lanterns represent joy, good fortune & social status. However, they are decreasing in popularity and most Malaysian young Chinese regard them as a dispensable decorative item for festivals. The usage of traditional Chinese hanging lantern is on the decline – studies have shown that the advent of modern lighting technology has thrown the production and useage of traditional Chinese lantern into crisis and turned it into an obsolete product. Through content analysis, researchers evaluated the current situation and explored the issues surrounding traditional Chinese hanging lanterns among young Chinese people. Results indicated that Malaysian young Chinese gradually lost interest in traditional Chinese hanging lanterns due to the lack of enthusiasm towards inherited Chinese culture and an increase in available exotic lighting accessories. This study may serve as a supplementary reference in the research and development of new cultural products, providing other researchers with a clearer direction to make their work easier and faster. Keywords: Traditional Chinese lanterns, Ramadan lanterns, anous, Kandeel